Structure and Function of Food Engineering - Amer Eissa, Ayman (IntechOpen, 2012)
This book conveys many significant messages for the food engineering and allied professions: the importance of working in multidisciplinary teams, the relevance of developing food engineering based on well-established principles, the benefits of developing the field by bringing together experts from industry, academia and government, and the unparalleled advantage of working as globally as possible in the understanding, development, and applications of food engineering principles. I am delighted to welcome this book to the Series and I am convinced colleagues from all parts of the world will gain great value from it.